Dataset for 'Vegans, vegetarians, fish-eaters and meat-eaters in the UK show discrepant environmental impacts' - Scarborough, P; Clark, M; Cobiac, L; Papier, K; Knuppel, A; Lynch, J; Harrington, R; Key, T; Springmann, M (University of Oxford, 2023)
These datasets provides the 1000 iterations of estimates of the environmental impact of vegans, vegetarians, fish eaters and meat eaters, aggregated at the level of age-sex-diet group. Development of these datasets is described in a research manuscript which can be accessed here: https://ora.ox.ac.uk/objects/uuid:332d8ffb-75cf-4f59-bded-bc2042de955d